Analysis Of Customer Relationship Management (CRM) Implementation On Student Satisfaction And Loyalty At Tutoring X - Yohanes Kurniawan; Mentiana Sibarani (UNIVED Press, 2025)
This study investigates the impact of Customer Relationship Management (CRM) implementation on student satisfaction and loyalty at Bimbingan Belajar X, a leading tutoring center in Indonesia. Despite its established reputation, the institution faces challenges such as low student retention rates and a lack of long-term commitment. Analysis indicates that only 40% of students maintain loyalty, significantly below the desired 75% target. The study identifies a trend where many students enroll primarily for short-term, exam-oriented preparation rather than continuous tutoring. To address these issues, the research emphasizes the importance of strengthening customer relationships through effective CRM strategies. By leveraging modern technology, including e-learning platforms and personalized learning systems like Item Response Theory (IRT), Bimbingan Belajar X can enhance communication, provide tailored learning experiences, and foster stronger connections with students. The findings suggest that improved CRM practices are crucial for increasing student satisfaction and loyalty, which are essential for maintaining a competitive edge in the increasingly competitive education sector. Without innovation and adaptation to evolving market demands, Bimbingan Belajar X risks losing its prominent position in the educational landscape.